56 A Quality Improvement Project to Assess and Refine the Handover Process at Morning Trauma Meetings. (28th February 2022) - Sadiq, S.; Tahir, M.; Elerian, S.; Baker, D.; Bruce, A.; Nur, I.; Malik, A.
Abstract: Aim: Poor handover and inadequate transmission of clinical information between shifts can result in patient harm. This study was designed to evaluate the impact of implementing a handover protocol on the quality of information exchanged in the trauma handover meetings in a UK district general hospital. Method: A prospective single centre observational study was performed at an acute NHS trust, using the define, measure, analyse, improve and control (DMAIC) methodology. Ten consecutive weekday trauma meetings, involving 43 patients, were observed to identify poor practices in handover. This data was used in conjunction with the Royal College of Surgeon's recommendations for effective handover (2007) to create a standard operating protocol (SOP). Following the implementation of the SOP, a further eight consecutive weekday trauma meetings, involving a further 47 patients, were observed. The data collection was performed by five trained independent observers. The data was analysed using t -test for quantitative variables and chi-square or Fisher's exact tests for categorical variables. Results: An improvement in the trauma handover was demonstrated in multiple aspects of handover including patient's past medical history, injury date, results, diagnosis, consent, mark and starvation status (all p < 0.001). Subgroup analyses showed that handover of neck of femur patients including information on mobility (p = 0.04), Nottingham Hip Fracture Score (p = 0.01), next of kin discussion (p = 0.075) and resuscitation status (p = 0.001) all improved following our interventions. Conclusions: These results demonstrate that the implementation of a well-structured handover protocol can improve the transmission of critical information in trauma meetings.